Estado actual de la investigación sobre Ipomoea carnea: toxicidad en ganado caprino - Sabogal, Ana (2007)
Ipomoea carnea from the dry forest of Peru appears undertwo sub-species: carnea and fistulosa. This study reviews thecauses of toxicity by Ipomoea carnea and its toxic effects oncaprine herds. The presence of swansonina and calysteginaalkaloids, and of selenium, are studied as causes of toxicity.The relationship between selenium distribution on soil and itsabsorption by plants in Jaguar Negro, Las Lomas y Coto deCaza El Angolo, in the departament of Piura, is studied.